PWE-195 Outcomes of Nutritional Assessment and Gastrostomy in Patients with Motor Neurone Disease (MND): A 4 Year Experience. (4th June 2013) - Gledhill, T; Lekharaju, V; Bliss, P
Abstract : Introduction: Motor neurone disease (MND) is a fatal, progressive, neurodegenerative disease with a median survival from onset of symptoms of 4.32 years. No controlled trials indicate a benefit, although current guidelines recommend gastrostomy tube placement when dysphagia or weight loss occurs. Changes in our local practise occurred in 2011 in order to reduce time to referral, we assessed the outcome. Methods: We reviewed records of all patients referred with MND to the nutrition team and analysed their outcomes including nutritional assessment, decision for gastrostomy, type and survival. Results: Since 2009, 76 patients were referred for nutritional assessment in MND. Nine were excluded (5 not reviewed; 4 re-referred). Baseline data: male 62.5%; mean age at diagnosis 63.9 years; mean body mass index (BMI) at referral 23.1kg/m 2 ; 75% had lost weight at review with mean weight loss of 17%. Non invasive ventilation (NIV) was used in 54% of patients. Forty-four patients (66%) consented to gastrostomy tube insertion. Ten patients (15%) declined and 13% of patients were not appropriate as MND was too advanced. In four patients (6%) tube placement was not yet indicated. Over 66% of patients had a radiologically inserted gastrostomy (RIG) tube and remainder a percutaneous endoscopic gastrostomy (PEG) tube. Patients had PEG placement if they had normal respiratory function (overnight oximetry, vital capacity and no NIV). Placement was unsuccessful in 3 patients (RIG 2; PEG 1); 2 had jejunostomy and one (RIG) declined further intervention. Five patients had complications; two (RIG) had pneumoperitoneum (managed conservatively); two had chest infections (RIG 1, PEG 1) and one had a site infection. 30-day (%) mortality as follows: no tube placed, 39; patient declined, 30; too unwell, 66; not yet indicated, 0. 1-year mortality (%) as follows: no tube placed, 74; patient declined, 70; too unwell, 78; not yet indicated, 25. Overall mortality (%) in tube placement as follows: 30-day, 11; 1-year, 57 (RIG, 30-days, 10; 1-year, 68; PEG, 30-days, 13; 1-year, 43). * Conclusion: Our results show high short-term mortality in all patients referred for nutritional assessment with MND, demonstrating the advanced stage of disease as nutritional status deteriorates. Mortality is lower in the PEG group; a reflection of less respiratory comorbidity or disease stage? Patients are being referred at earlier stages in their disease; appropriately identifying patients who benefit may provide better outcomes. Disclosure of Interest: None Declared.